Impact plastic crushing and design of density-graded cellular materials. (March 2016) - Zheng, Jie; Qin, Qinghua; Wang, T.J.
Highlights: The impact responses and the energy absorptions of different density-graded cellular rods are investigated theoretically and numerically. More than two shock fronts appear in the middle-low rod. Suggestions are given for designing energy absorbing structure. Abstract: One-dimensional impact response of density-graded cellular rods with middle-low and middle-high density distributions is investigated theoretically and numerically. Analytical model based on shock-wave theory is proposed to predict impact response of density-graded cellular rods. The refined finite element calculations are performed using the periodic voronoi structures and agree well with the analytical predictions. It is found that there are two shock fronts in the density-graded rod with middle-high distribution while three shock fronts in the density-graded rod with middle-low distribution. Comparisons of the energy absorption capacity and the stress of the two ends of the rods show that the various gradient distributions may provide multiple selection schemes in the design of the prototypical multifunctional cellular systems.